An ethnographic evaluation of a speciality training pathway for general practice nursing in the UK. (July 2022) - Mann, Claire; Boyd, Matthew; Davis, Heidi; Beardmore, Gillian; Hinsliff-Smith, Kathryn
Abstract: Aims: The aim of the study was to evaluate the implementation and impact of the General Practice Nurse – Specialty Training (GPN-ST) programme across seven sites in one geographical location in the UK. The objectives were to understand, describe and evaluate: 1) the implementation of the 'proof of concept' training scheme; 2) the learning undertaken during the training; and 3) the impact of the training scheme on individual nurses. These objectives offer the opportunity to describe the potential return on investment for General Practices supporting nurses new to General Practice through the programme. Background: General Practice Nurses (GPNs) play a vital role in delivering primary and community care. In the UK there is a shortfall in the GPN workforce. Unlike training for other clinical professions there is currently no standardised training pathway or entry route for nurses wishing to work in General Practice. An ethnographic evaluation was undertaken of a one-year speciality training programme (GPN-ST). The programme, aimed at nurses new to General Practice, included formal higher education training and funded supported learning and mentoring whilst in practice. Methods: A qualitative ethnographic evaluation was undertaken. Observations were conducted of programme implementation, network and education meetings in the scheme. In-depth, semi-structured, interviews and focus groups were conducted with a wide range of professionals (n = 40) including nurse mentors, nursing students, academic providers, commissioners and the programme managers. These data were supplemented by documentary analysis of meeting notes, learning materials, internal student feedback and locally collected evaluation material in line with ethnographic approaches to research. Kirkpatrick's model for course evaluation and complimentary inductive emergent thematic analysis was used. Findings: There is evidence of learning at every level of the Kirkpatrick model from reaction through to changes in behaviour and results in practice for patients. The speciality training route offered opportunities for deep learning for GPNs. The scheme offered a comprehensive career pathway to General Practice nursing which in turn benefited General Practices. Practices benefitted from confident, independent nurses who were able to contribute to patient care, practice safely and also contributed widely in the long-term for example in research, workforce development and mentoring. Conclusions: General Practice needs to invest in developing a workforce of GPNs, there are significant benefits to investing in the development of GPNs through a training pathway. This scheme provides scope for application in other clinical settings as well in other countries where there is a gap in career progression into GP practices. Tweetable abstract: GPNs play a vital role in delivering primary and community care. Unlike training for other clinical professions there is currently no standardised training pathway or entry route for nurses wishing to work in General Practice. There are significant benefits to investing in the development of GPNs through a training pathway